Biological preparations against bacteriosis white cabbage - Borzykx, A.I.; Tkalenko, G.N. (Interdepartmental Thematic Scientific Collection of Phytosanitary safety, 2016)
Based on years of research results the prevalence of vascular and mucosal bacteriosis white cabbage in the Steppe-Zone of Ukraine. The effective of microbial preparations of Trichoderma, Rizoplana, Gaupsina and their mixtures against bacteriosis.